OASIS high-resolution integral field spectroscopy of the SAURON ellipticals and lenticulars - McDermid, R; Emsellem, E; Cappellari, M; Kuntschner, H; Bacon, R; Bureau, M; Copin, Y; Davies, R; Falcon-Barroso, J; Ferruit, P; Krajnovic, D; Peletier, R; et al. (2004)
We present a summary of high-spatial resolution follow-up observations of the elliptical (E) and lenticular (SO) galaxies in the SAURON survey using the OASIS integral field spectrograph. The OASIS observations explore the central 8" x 10" regions of these galaxies using a spatial sampling four times higher than SAURON, often revealing previously undiscovered features. Around 75% (31/48) of the SAURON E/SOs with central velocity dispersion greater than or similar to 120 kin s(-1) were observed with OASIS, covering well the original SAURON representative sample. We present here an overview of this follow-up survey, and some preliminary results on individual objects, including a previously unreported counter-rotating core in NGC4382; the decoupled stellar and gas velocity fields of NGC 2768; and the strong age gradient towards the centre of NGC 3489.